THE INFLUENCE OF WORK ENVIRONMENT ON JOB SATISFACTION WITH MOTIVATION AS MEDIATION IN KARAWANG CITY - Fipin kirani; Sari Marliani; July Yuliawati (Journal Of Resource Management, Economics And Business, 2024)
Purpose: To analyze the influence of the work environment on job satisfaction with motivation as mediation at BKPSDM Karawang. Research Methodology: Descriptive quantitative verification, saturated sample of 53 employees, multiple linear regression using SPSS v.25.. Results: 1) Good work environment, 2) Good work motivation, 3) Good job satisfaction, 4) Partial influence of work environment on job satisfaction, 5) Partial influence of work motivation on job satisfaction, 6) Simultaneous influence of work environment and work motivation on job satisfaction.. Limitations: The study was conducted only at BKPSDM Karawang. Contribution: This study can be useful for organizations in the public sector to understand the influence of work environment and motivation on job satisfaction.